Double Standards in Educational Standards: Are Disadvantaged Students Being Graded More Leniently? - Oliver Himmler; Robert Schwager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
A simple model of decentralised graduation standards is presented. It is shown that a school whose students are disadvantaged on the labour market applies less demanding standards because such students have less incentives to graduate. The model's predictions are tested using Dutch school-level data. Since students in the Netherlands have to participate both in a central and in a school specific examination, we can identify the grading policy of individual schools. We find that schools which harbour greater shares of disadvantaged students tend to set lower standards. This effect is largest in the branch of secondary schooling preparing for university.
Keywords: I21; J15; 330; education; grading; social status; schools; Netherlands